Impact of agricultural sector on economic growth in Selangor, Malaysia - Mohd Kamal, Muinnudin (2018)
Selangor has the highest population density in Malaysia and the population growth in this state is also found to be highest. To support the population growth, the quantity of food production also needs to grow at a parallel rate so that the food supplies can adequately accommodate the growing population in Selangor. However, the growth rate of food production in Selangor is neither stable nor parallel to the population growth rate. The total contribution of the agricultural sector to the economic growth in Selangor declined in 2015 compared to 2010. The significance gaps between the growth rates of population and food production should be reduced as far as food security is concerned. Why is the agricultural sector in Selangor less important? Is the sector associated with lower economic impacts in the state? Therefore, this study attempts to examine the impact of the agricultural sector for the sectoral growth and development of economy in Selangor. For this purpose, this study develops a multi-sectoral database for Selangor that provides inter-industry linkages between the agricultural sector and the rest of the sectors in the state. Such database can be achieved by build a regional input-output table (RIOT) for Selangor. By using RIOT, direct and indirect impacts of growth in the agricultural sector are measured by modelling a value-added multiplier. Results demonstrated that an indirect value-added multiplier effect for the agricultural sector is more dominant than a direct multiplier. This reflected that the agricultural sector has a high degree of integration compared to other sectors and has the potential to generate substantial returns from investment activity as well as stimulate the growth of the sector that acts as an input provider to it. Altogether, this study provides a clear indication that the agricultural sector is not only important for the growth and development in Selangor, but also vital for supporting the population growth.